AICCRA-Zambia Intermediate Project Indicators Progress Report 2025 - Jacobs-Mata, Inga; Kakwasha, Keagan; Mudege, N.N.; Omondi, J. O; Sibeso, C; Amarnath, Giriraj; Umer, Yakob; Ram, Dhulipala; Moyo, Martin; Abdul, Matin. Md; Mulundu, Stephen; Mapedza, Everisto (2025)
This report provides highlights of the key achievemenst AICCRA Zambia has delivered in 2025 against the targets for each intermediate project indicators